Sob o fogo cruzado das campanhas: ambientalismo, comunicação e agricultura familiar na prevenção ao fogo acidental na Amazônia - COSTA, Luciana Miranda (Universidade Federal do Pará, 2011)
This Doctorate research began in 2000 and its theme is the accidental fire in the Amazon forest and, in particular, in the state of Pará. The object of study are the educational and outreach campaigns to prevent the accidental fire, involving the production, circulation and reception of information. They were implemented by governmental and non-governmental organizations, especially from 1998 onwards. Four projects and their respective campaigns were chosen in order to compose the analysis corpus: the “Proteger”, the “PGAI Queimadas”, the project Bom Manejo do fogo and the project “Fogo Emergência Crônica”. The campaigns have very similar elements related to the theoretical and methodological aspects, regarding their public, their goals, the kind of material produced (such as primers and posters) and the involved geographical areas. This thesis aims to show how the relations of power among the social agents from environmental institutions and from small agricultural institutions were established. Besides, it intends to demonstrate the different strategies and tatics carried out by small farmers and their representative institutions (as Rural Workers Unions and associations) to rebuild campaign discourses and state their position in the symbolic fight. The main hypothesis of this research, which makes use of Bourdieu’s theoretical concepts, is that there is a “tension” between different point of view issues coming from environmental agents and institutions and the ones from agricultural family representation. So, the communication relations established by campaigns are relations of power that emphasize the “imbalance” between these two fields. The result is the temporary and partial reach of the main purposes of those campaigns; that are: reduction in the number of “accidental fire” occurrences, caused by agricultural fire and permanent use of prevention techniques by small farmers.